PENGARUH INTENSITAS SUPERVISI KEPALA SEKOLAH TERHADAP KOMPETENSI PEDAGOGIK GURU DI SDN 32 BALANG CADDI PANGKEP - Rusnaeni Bahar; Muh. Yunus; A. Mulyadi Radjab (Jurnal Education and Development, 2022)
The study aimed to describe: (1) the intensity of the supervision of the principal at SDN 32 Balang Caddi Pangkep, (2) the pedagogical competence of teachers at SDN 32 Balang Caddi and (3) the effect of the intensity of the principal's supervision on the pedagogical competence of teachers at SDN 32 Balang Caddi. Pangkep. The type of research used was a descriptive quantitative research. The populations in the study were all teachers at SDN 32 Balang Caddi Pangkep. The sampling technique in the study was a saturated sampling, so the total samples as a whole were 11 teachers. The data collection technique used was a questionnaire as primary data, and documentation as supporting data. Techniques of data analysis was carried out by analyzing the results of respondents' answers to the questionnaire quantitatively using descriptive analysis in the form of percentages and inferential analysis using analyst prerequisite testing the hypothesis test and test of the coefficient of determination. The results showed thats: (1) the description of the intensity of the supervision of the principal at SDN 32 Balang Caddi Pangkep as a whole was in the high criteria, where the highest score of 90.2% was on the indicator of the intensity of supervision planning, while the lowest value of 67.4% was on the indicator of the intensity of follow-up supervision, (2) the description of the pedagogical competence of teachers at SDN 32 Balang Caddi Pangkep as a whole was in the high criteria, where the highest score of 88.6% was on the indicator of understanding of students, while the lowest score of 65.9%, was on the learning evaluation indicators, and (3) there was a significant effect of the intensity of the principal's supervision on the pedagogic competence of teachers at SDN 32 Balang Caddi Pangkep, where the probability value was 0.03 < 0.05 significant value and the t value was 1.934 > t table 1.833.